An Innovative Method of Storing Live Cocoons and its Impact on the Quality and Technological Indicators of Live Cocoons (Texas Journal of Multidisciplinary Studies, 2023)
This article presents the results of scientific research in the field of development of invasive technology for storing live silkworm cocoons grown by re-feeding in the worm water of the Uzbek Research Institute of Natural Fibers. As well as the results of research to determine the impact of innovative technology for storing live cocoons on the qualitative and technological indicators of live cocoons. Determination of qualitative and quantitative indicators live cocoons were produced with honey of a single unwinding on a laboratory machine for single unwinding of cocoons of the LC system of the UzNIISHP system in the laboratory conditions of the accredited testing laboratory of UzNIINV. After each season of re-feeding, live cocoons were unwound on the LC laboratory machine and the technological parameters of live cocoons were determined. Live cocoons removed from cocoons were stored on special refrigeration units at temperatures of +2, +4 and +8 ° C and after 10, 20 and 30 days of storage, the technological parameters of live cocoons were determined.